MANIPULASI LABA DI SEKTOR KESEHATAN: STUDI SEBELUM, SAAT, DAN SESUDAH PANDEMI COVID-19 DI INDONESIA - Sakti, Eklamsia; Faizah, Yustin Nur; Maduratna, Enggal Sari (Universitas Airlangga, 2024)
This research aims to explore indications of earnings manipulation during the Covid-19 pandemic. The subject of this research concerns companies in the health sector listed on the Indonesia Stock Exchange (BEI). Tools to measure indications of earnings manipulation use the Earnings Quality Ratio, Revenue Quality Ratio, Accruals Earnings Management, Real Earnings Management, Beneish M-score model, and DechowF-score model. Based on the research results, this study reached three main conclusions. First, indications of earnings manipulation continue to increase between 2018 and 2022. Second, when the pandemic hit, earnings manipulation saw a significant increase, especially in 2021. Third, once the pandemic ended, indices There were still many cases of earnings manipulation, including manipulation of earnings quality, recording of false income, poor cash flow, production expenses and costs.